ENHANCED FOOD INTAKE SUPPRESSION AND BODY MASS REDUCTION WITH COMBINED L-NAME AND LEPTIN ADMINISTRATION IN FASTED RATS - M.Hristov (Trakia Journal of Sciences)
PURPOSE: This study aimed to investigate the effect of combining Nω-Nitro-L-argininemethyl ester (L-NAME) and leptin on food intake and body mass gain in fasted rats, as both have been shown to suppress food consumption. Additionally, the study evaluated the impact of L-NAME on fever induced by leptin. METHODS:L-NAME and recombinant rat leptin were administered intraperitoneally, both alone and in combination, to fasted rats. Measurements included monitoring body temperature via rectal thermocouple probes, and assessing food intake and body mass gain 24 hours post-injection. RESULTS: Systemic administration of L-NAME (50 mg/kg, i.p.) abolished the febrile response elicited by leptin. Furthermore, administering leptin (0.5 mg/kg, i.p.) and L-NAME (50 mg/kg, i.p.), alone or in combination, suppressed food intake and body mass gain in fasted rats after a 24-hour period. Notably, combining leptin and L-NAME had a more pronounced effect on food intake suppression and body mass loss than using either drug alone. CONCLUSIONS: It could be speculated that the combination of leptin and L-NAME might potentially serve as an effective treatment for obesity, given their enhanced effects on food intake suppression and body mass loss observed in the study. Additionally, these results suggest a clear involvement of nitric oxide synthase during leptin-induced fever.